Food Coma Is Real: The Effect of Digestive Fatigue on Adolescents' Cognitive Performance - Justine Hervé; Subha Mani; Jere R. Behrman; Ramanan Laxminarayan; Arindam Nandi (Institute of Labor Economics (IZA), 2024)
Food coma, also known as postprandial somnolence, is a commonly cited reason for experiencing reduced alertness during mid-afternoon worldwide. By using exogenous variation in the timing of tests and, hence, by extension, plausibly exogenous variation in the temporal distance between an individual's last meal and the time of test, we examine the causal impact of postprandial somnolence on cognitive capacities. Analyzing novel time use data on ~ 4,600 Indian adolescents and young adults, we find that testing within an hour after a meal reduces test-takers' scores on English, native language, math, and Raven's tests by 8, 8, 8, and 16 percent, respectively, compared to test-takers who took the tests more than an hour after their meal. We further find that the negative effect of postprandial somnolence on cognition operates through increased feelings of fatigue and depletion of cognitive resources that become more pronounced while dealing with more challenging test questions.
Keywords: I12; I18; I21; J24; 330; post-meal fatigue; cognitive skills; low-stakes tests; India; adolescents